These final hours [videorecording (DVD)] - Hilditch, Zak; Snook, Sarah; De Gouw, Jessica, 1988-; Phillips, Nathan (Well Go USA Entertainment, 2015)
A self obsessed man makes his way to a huge crazy party on the last day of Earth but ends up saving the life of a little girl who is searching for her father. Their relationship ultimately leads him on the path to redemption.